Monitoring students’ metacognition in KSSR classroom - Wirawani Kamarulzaman,; Rosnani Hashim, (2019)
The ability to think critically is essential for students to face the challenges of the 21st century. Students should be equipped with the skills as those skills will help them to solve problems, make wise decisions and analyse information. One of the approaches to cultivate critical thinking is by monitoring their metacognition. Thus, the purpose of the study is to explore the methods of monitoring students’ metacognition used by teachers in KSSR (Primary School Standard Curriculum; Kurikulum Standard Sekolah Rendah) classroom. Six primary school teachers were purposely selected in the study. Qualitative design was utilised where they were interviewed separately and probing was done to elucidate or illuminate the issue of study. Observation was also done as a method for methodology trigulation. The data from both sources was recorded and transcribed. Data coding was used to analyse the data where the transcribed text was segmented and labelled to form descriptions, main ideas as well as themes. These emerging themes were analysed and interpreted. The findings suggest that the studentcentred approach exercised in the curriculum has enabled students to share and discuss information among them. The teaching techniques which include questioning approach, asking students to predict outcome and provide reasons were also employed. Formative assessment such as indirect questioning with diverse assessments were also exercised in monitoring students’ thinking about thinking or metacognition. (Abstract by authors)